Metabolic disorder index as predictor of performance in endurance horses - Mohd Rajdi, Nur Zul Izzati (2017)
Endurance is a type of equestrian sport that is recognized by the Fédération Equestre Internationale (FEI). It is a long-distance race ranging from 40 to 120 km and is divided into several loops whereby each loop covers from 20 to 35 km. The performance of endurance horses is usually evaluated on their ability to complete the race in the shortest period. The rate of elimination of horses in the races are still high, ranging from 10% to 60%. Endurance horses are usually eliminated from the race due to lameness, metabolic disorders, and other causes which include failure to reach at the veterinary inspection within the stipulated period, optional withdraws, and concerns over the well-being of the horse. A prediction of horses’ performance before the race can help reduce the rate of elimination as well as care for their well-being by preventing the participation of poor performance horses in the competition. Therefore, the purpose of the present study is to determine the current completion and elimination rate of endurance races in Malaysia. A total of 194 endurance horses who participated in 12 endurance races organized in several states in Malaysia from May 2015 until December 2016 are involved. Out of the 194 horses, 188 are from Terengganu while 6 are from Kelantan. From the total of 194 horses, 126 are able to complete the race while 68 of them are eliminated from the race by official veterinarians. In the current study, 35.05% of the horses are eliminated and 64.95% of them are able to complete the race successfully. Among the eliminated horses, 54.41%, 29.41% and 16.18% of them are due to lameness, metabolic disorders and other causes respectively. Most of the eliminated horses competed in the 80 km race while those who successfully completed the race competed in the 40 km race. The average speed for good, moderate, and poor performance horses is 15.72 ± 2.9, 12.19 ± 2.1, and 13.91 ± 2.6 km h-1 respectively. In the 40, 80, and 120 km races, the average speed is 12.65 ± 1.8, 15.99 ± 3.5, and 12.86 ± 0.2 km h-1 respectively showing that the horses performed fastest in the 80 km races. This data could be of assistance to the veterinarians in monitoring the trend of endurance races in Malaysia and improve the current management practices to reduce the rate of elimination in subsequent races. However, the elimination of the horses is unpredictable because there is no specific method to predict their performance before the race. In 2017, Adamu et al. came out with the Metabolic Disorder Index (MDI) which claims can be used in predicting a horse’s performance before the race. The MDI is defined as a product of packed cell volume (PCV), creatine kinase (CK), and interleukin-6 (IL-6) divided by the product of chloride (Cl-) and glutathione reductase (GR) multiplied by 100. A prediction is made based on the MDI value. Horses who have MDI value of >5.5 is predicted to be of good performance while those who have MDI value of <5.5 is predicted to be of poor performance. However, this index has not been tested on the field under controlled conditions. Other purpose of this study is to evaluate the MDI’s parameters of good and poor performance endurance horses before the race and to validate the MDI as a predictor for horses’ performance in endurance races. Out of the 194 horses that are involved in the study, only 54 of them are selected for blood sampling to test the validity of MDI. Blood samples are taken a day prior to the event to determine the packed cell volume (PCV), chloride (Cl-), and Interleukin-6 (IL- 6) concentrations as well as creatine kinase (CK) and glutathione reductase (GR) activities. These parameters are used to determine the MDI in endurance horses at rest one day before the competition. Poor performance horses have significantly (p<0.05) higher serum CK concentrations at 216.0 ± 65 U L-1 compared to good performance horses at 150.7 ± 29 U L-1. The serum Cl ̄ concentration in poor performance horses is lower at 99.8 ± 5.6 mmol L-1 compared to good performance horses at 103.7 ± 3.3 mmol L-1. The study shows that MDI has a high ability to identify poor performance horses with approximately 90% sensitivity. However, in terms of accuracy, it is more accurate in predicting good performance horses with a negative predictive value of 90.91%.